Formação da identidade profissional das mulheres no ensino superior: currículo e relações culturais de gênero - Galvão, Sarah Fantin de Oliveira Leite (2018)
The main question researched in this thesis is regarding the responsibility of higher education curriculum in making a consistent women professional identity formation and empowering them for the labor market. It is verified that the present gender relations, associated to social and educational cultures influence Brazil’s women professional identity formation. These question lead to postponing the personal and familiar life development, favoring the construction of a professional career permeated by discrimination both in hierarchical growth as in wage inequalities. The present thesis has as main objective to understand how the higher education curriculum can empower women to face the inequalities of gender cultural relations in the labor market to warrant her rights and the pursuit for equality and social justice. To deepen this approach, Brazil’s gender cultural relation was analyzed: in which ways women are considered by the labor market, economy and laws, how the cultural paradigms influence women professional identity formation and how the professional identity formation influence in warranting the Rights and social justice for women. For that, a qualitative research was performed, through bibliographical survey and field research and analyzed based on the main support authors: Boaventura de Souza Santos, Foucault, Bourdieu and Jurjo Torres Santomé